Effects of bubbler irrigation frequency on yield and quality of foster grapefruit under Khartoum State conditions - Khalifa, Ahmed; Hamed, Ibtihal; Ahmed, Shaker; Ali, Mohamed; Ahmed Ali, Imad-eldin; Heng, Lee Heng; Bakheit, Salah (Gezira Journal of Agricultural Science, 2017)
The experiment was carried out in private orchards at Tayba Alhasnab area of south Khartoum, Sudan, ( latitude 15° 35´ N, longitude 32° 60´ E, altitude 380 masl) during 2013 and 2014 to study the effects of bubbler irrigation frequency on yield and quality of grapefruit under Khartoum State conditions . Five different frequencies of irrigation were applied at 3, 5, 7, 9 and 12 days. Treatments were replicated 4 times in a randomized complete block design (RCBD) and each plot encompassed 3 trees. The results revealed that higher yield and number of fruits per tree were obtained with 5 days irrigation frequency in both years. The 5 days irrigation frequency increased total yield of foster grapefruit by 39% and 8% in the first and second year, respectively, compared to the 12 day. The highest fruit weight was obtained with 5 days irrigation frequency in both years. Moreover, irrigation frequency every 5 days had the highest water productivity.         أجريت التجربة في بستان خاص في منطقة طيبة الحسناب جنوب الخرطوم، السودان خلال الفترة من 2013  وحتي 2014 لدراسة اثر تكرار الري الفقاعي علي انتاجية وجودة القريب فروت فوستر تحت ظروف ولاية الخرطوم. تم تطبيق خمسة معاملات مختلفة من فترات الري (3 و 5 و 7 و 9 و 12 يوم) وتكرارها في اربعة مرات علي نظام المربعات العشوائية الكاملة وشملت كل قطعة 3 أشجار. وأظهرت النتائج أن الانتاجية العالية وعدد الثمار لكل شجرة تم الحصول عليها مع تكرار الري كل 5 أيام في كلا العامين. تكرار الري كل 5 ايام ادي الي زيادة انتاجية القريب فروت بنسبة 39% و8% في السنة الاولي والثانية علي التوالي مقارنة بتكرار الري كل 12 يوم. اعلي وزن للثمرة حصل عليه مع تكرار الري كل 5 ايام في العامين. اضافة الي ذلك ادي تردد الري كل 5 ايام  الي أعلى إنتاجية لوحدة المياه.